A Sustainable Approach to Glucose Biosensors: Utilizing Coconut Shell Activated Carbon and NiCaFe₂O₄ Nanoparticles - Fatoni Amin; Hutama David; Hermawan Dadan; Samanman Saluma; Dwi Anggraeni Mekar (E3S Web of Conferences)
Diabetes-related mortality can be significantly reduced through early detection of blood glucose levels. This study presents a sustainable approach to glucose biosensors by utilizing coconut shell activated carbon as the working electrode material in a carbon paste electrode for electrochemical glucose detection via cyclic voltammetry. The performance of the electrode was further enhanced with NiCaFe₂ O₄ nanoparticles to improve electron transfer and redox potential. The optimized electrode consisted of a 2:1 ratio of activated carbon to paraffin, incorporating 16% NiCaFe₂ O₄ nanoparticles. Detection of hydrogen peroxide using this modified electrode exhibited an oxidation peak at 0.16 V and a reduction peak at -0.35 V. Optimal glucose detection conditions were achieved in 100 mM phosphate buffer at pH 7.5. Glucose oxidase was immobilized on the modified electrode, showing a linear response for glucose detection at the oxidation peak of 0.66 V. This sustainable biosensor demonstrated high sensitivity and potential for low- cost, eco-friendly glucose monitoring applications.